Sa taṅʻʺ cā myāʺ pro prā taiʹ cacʻ tvaṅʻʺ Ḅamā praññʻ - Lha, Lū thu Ūʺ, 1910-1982 (Lu thu Ūʺ Lha, 1969)
Collection of reportage on politics and government in Burma during the Second World War, 1939-1945.